2017
DOI: 10.3168/jds.2016-11620
|View full text |Cite
|
Sign up to set email alerts
|

Epimural bacterial community structure in the rumen of Holstein cows with different responses to a long-term subacute ruminal acidosis diet challenge

Abstract: Subacute ruminal acidosis (SARA) is a prevalent metabolic disorder in cattle, characterized by intermittent drops in ruminal pH. This study investigated the effect of a gradual adaptation and continuously induced long-term SARA challenge diet on the epimural bacterial community structure in the rumen of cows. Eight rumen-cannulated nonlactating Holstein cows were transitioned over 1 wk from a forage-based baseline feeding diet (grass silage-hay mix) to a SARA challenge diet, which they were fed for 4 wk. The S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
86
2
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(103 citation statements)
references
References 59 publications
9
86
2
4
Order By: Relevance
“…Previous studies showed that a long‐term HG diet appeared to disrupt the balance of the ruminal microbiota and affect the rumen health of dairy cattle and goats (Hua et al, ; Wetzels, et al, ). In the present study, the HG diet increased the richness of bacterial communities of jejunal mucosa, but it seemed to have no apparent effect on the richness of bacterial communities of ileal mucosa, with no significant between‐group difference observed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that a long‐term HG diet appeared to disrupt the balance of the ruminal microbiota and affect the rumen health of dairy cattle and goats (Hua et al, ; Wetzels, et al, ). In the present study, the HG diet increased the richness of bacterial communities of jejunal mucosa, but it seemed to have no apparent effect on the richness of bacterial communities of ileal mucosa, with no significant between‐group difference observed.…”
Section: Discussionmentioning
confidence: 99%
“…The representative OTU5 associated with unclassified Sphingobacteriaceae as MRO predictors were negatively with macronutrients intake and VFA production. OTU5 classified as Olivibacter sitiensis function is not clear, but it decreased with pH reduction when intake high concentrate diet (25). The species affiliated with Prevotella (OTU2, OTU3, OTU6 and OTU13) in top 30 increased in solid supplementary regimes.…”
Section: Discussionmentioning
confidence: 99%
“…Some research reported that high concentrate feeding induces the incidence of sub-acute ruminal acidosis (Mickdam et al 2016;Wetzels et al 2016;Sato 2016). Mickdam et al (2016) studied the effects of feeding 60:40% grain and forage ratio with NDF content of 31.8% and Wetzels et al (2016) investigated feeding 65:35% grain and forage ratio with NDF content of 256 g/kg and Sato (2016) investigated 80:20% of grain and forage ratio.…”
Section: The Importance Of Feeding High Concentrate Diet and Metabolimentioning
confidence: 99%
“…Different from SARA, acidosis is characterized by a prolong period of pH decrease below these thresholds (pH <5.0) (Nagaraja & Lechtenberg 2007). It is worth noting that there are quite a lot of pH thresholds have been used to illustrate SARA (Plaizier et al 2008;Zebeli et al 2008;Gimeno et al 2015a;Wetzels et al 2016). Most of the studies mentioned that ruminal pH dropped between 5.6 and 5.8 for three hours to 5.4 hours per day (Plaizer et al 2008;Zebeli et al 2008;Wetzels et al 2016).…”
Section: The Importance Of Feeding High Concentrate Diet and Metabolimentioning
confidence: 99%
See 1 more Smart Citation